Pengelolaan Dana Bantuan Operasional Sekolah (BOS) dengan Konsep Spiritualitas Sekolah Dasar di Kabupaten Karangasem - Ni Luh Putu Nita Yulianti; Tini Adiatma (Bulletin of Community Engagement, 2024)
This research investigate the management of School Operational Rock (BOS) funds with a spiritual concept seen from the accountability and transparency of School Operational Rock (BOS) fund reports. Data collection was carried out using in-depth interview methods. The selection of informants was determined using purposive sampling techniques and verifying the validity of the analysis results using source triangulation. The research results show that accountability and transparency cannot only be assessed based on School Operational Assistance (BOS) reports but should look at the management of human resources, namely the School Operational Assistance (BOS) management team who have minimal knowledge of Technology and Accounting in making reports so that Special personnel are required who have skills in the IT field. Furthermore, conflict management (differences in interests) can occur between the principal and treasurer in some schools, this can be caused by personal problems or lack of communication within the school environment and can affect the management of School Operational Funds (BOS), with the existence of trust. By applying the teachings of Hinduism in managing School Operational Assistance (BOS) fund reports, adhering to Hindu beliefs, namely Tri Kaya Parisuda (kayika, manacika, and wacika) and the Karmaphala Law, it is believed that it will produce accountable and transparent reports with good spiritual management from the team. Management of School Operational Rocks (BOS).